The athlete biological passport - Saugy, M. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
The Athlete biological passport (ABP) is an individual and longitudinal follow up in the fight against doping which came naturally with the implementation of tests out of the competition period of the athletes. For an individual, it has been observed that the homeostasis of biosynthesis and metabolism of endogenous hormones was not disturbed by sports activity, but of course will be influenced by the intake of similar substances. Actually, the passport has been defined as an individual and longitudinal observation of biomarkers. These markers need to belong to the biological cascade influenced by the application of forbidden hormones or more generally, affected by biological manipulations which can improve the performance of the athlete. Nowadays, only the hematologic passport of an athlete has been officially set up. This is a statistical representation of the longitudinal follow up of some blood biomarkers. This individual and longitudinal follow up of blood parameters is of interest, because the intra-individual variability is lower than the corresponding inter-individual variability. Among the key points for the implementation of the athlete biological passport is its possibility to resist to the legal and scientific challenges. The ABP should be implemented in the most possible transparent way in the process and with the necessary independence between planning, interpretation and result management of the passport. To reach this transparency and efficiency, a new major actor has been introduced in the system to create a framework of independence: The athlete Passport Management Unit (APMU). The World Antidoping Agency (WADA) did implement new dedicated technical documents associated to the passport (hematological module). This was done in order to allow a correct implementation of a profile which can resist to any scientific or legal critics in following strictly some steps in the chain of production of the results and in the management of the interpretation of the passport. Four technical documents have been then associated to the guidelines which correspond to the requirements for passport operation. The ABP will be completed very soon by the steroid profile module. The same philosophy of individual and longitudinal follow up will be applied and the interpretation steps will also be managed by a specific APMU in a similar way as applied in the hematologic module. Thus, after exclusion of any possible pathology, specific deviations from the individual norms would be then considered as a potential manipulation of performance with hormones or other modulators.